2018
DOI: 10.1007/s00592-018-1223-y
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy in the treatment of diabetic foot ulcers may be mediated through differential gene expression

Abstract: We found initial evidence that the NPWT effect on DFUs may be mediated through differential gene expression. A discovery of the specific molecular mechanisms of NPWT is potentially valuable for its clinical application and development of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…On the molecular level, NPWT promotes proangiogenic and anti-inflammatory conditions by increasing the expression of growth factors and reducing the expression of inflammatory cytokines [26]. In our previous reports, we saw that NPWT altered the local gene expression involved with wound healing [4]. Moreover, we showed that NPWT's action is mediated through epigenetic alterations resulting mainly in the inhibition of complement system activation [5].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the molecular level, NPWT promotes proangiogenic and anti-inflammatory conditions by increasing the expression of growth factors and reducing the expression of inflammatory cytokines [26]. In our previous reports, we saw that NPWT altered the local gene expression involved with wound healing [4]. Moreover, we showed that NPWT's action is mediated through epigenetic alterations resulting mainly in the inhibition of complement system activation [5].…”
Section: Discussionmentioning
confidence: 97%
“…Negative pressure wound therapy (NPWT) has been used as an adjunct treatment for DFUs. Its potential influence on local gene expression and epigenetic methylation in the wound bed has been recently described [4, 5]. However, NPWT's novel mechanism of action may be associated with processes involving the entire organism where signals are transmitted via circulating molecules between the organism's tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
“…The patients included in this prospective clinical observation were participants of the research project on the molecular mechanisms of NPWT [ 13 ]. The total study group consisted of 75 consecutive patients with T2DM and concomitant foot ulceration(s) treated between 2014 and 2018 in the Department of Metabolic Diseases of the University Hospital in Krakow, a tertiary academic outpatient center for patients with DFS in southern Poland.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported our results on the effect of NPWT on gene expression as assessed by microarray technology in patients with type 2 diabetes and DFU in comparison with standard therapy. We identified four genes that were differentially expressed—GFRA2 (GDNF family receptor alpha‐2), C1QBP (complement C1q binding protein), RAB35 (member of RAS oncogene family) and SYNJ1 (synaptic inositol 1,4,5‐trisphosphate 5‐phosphatase 1) . Interestingly, all four genes seemed to be functionally involved in wound healing by influencing re‐epithelialization and angiogenesis.…”
Section: Negative Pressure Wound Therapy Molecular Mechanismsmentioning
confidence: 99%
“…We identified four genes that were differentially expressed-GFRA2 (GDNF family receptor alpha-2), C1QBP (complement C1q binding protein), RAB35 (member of RAS oncogene family) and SYNJ1 (synaptic inositol 1,4,5-trisphosphate 5-phosphatase 1). 58 Interestingly, all four genes seemed to be functionally involved in wound healing by influencing re-epithelialization and angiogenesis. They were not reported earlier as genes potentially related to NPWT action.…”
Section: Therapy Molecular Mechanismsmentioning
confidence: 99%